2023
DOI: 10.1029/2022jg007160
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Leaf Reflectance Spectra Across the California Flora Partitioned by Evolutionary History, Geographic Origin, and Deep Time

Abstract: Evolutionary relatedness underlies patterns of functional diversity in the natural world. Hyperspectral remote sensing has the potential to detect these patterns in plants through inherited patterns of leaf reflectance spectra. We collected leaf reflectance data across the California flora from plants grown in a common garden. Regions of the reflectance spectra vary in the depth and strength of phylogenetic signal. We also show that these differences are much greater than variation due to the geographic origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Past research on remote sensing of evolutionary history with spectral information relied primarily on field or leaf spectroscopy ( 11 14 , 60 ). Field-collected spectra represent nearly optimal data, are collected to represent pure spectral signatures of a target, and do not have positional error, or atmospheric interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research on remote sensing of evolutionary history with spectral information relied primarily on field or leaf spectroscopy ( 11 14 , 60 ). Field-collected spectra represent nearly optimal data, are collected to represent pure spectral signatures of a target, and do not have positional error, or atmospheric interference.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that VSWIR (visible-to-short wavelength infrared; 400-2,500 nm) reflectance properties of vegetation capture evolutionarily conserved biochemical, structural, and other functional attributes of plant species (e.g., refs. ( 11 14 )). Yet, phylogenetic turnover and diversity have not been fully explored as alternative methods for assessing biodiversity from space.…”
mentioning
confidence: 99%
“…Spectral diversity or spectral dissimilarity from experimental plots also increases with evolutionary divergence time and was linked to variation in productivity (Schweiger et al., 2018). Phylogeny‐based approaches have enabled the partitioning of sources of spectral variability in regional floras (Griffith, Byrd, Anderegg, et al., 2023) and the mapping of dominant plant lineages (Griffith et al., 2023a, 2023b). Most studies showing phylogenetic conservatism in leaf spectra, however, are limited to single sites and few sampling periods despite recognition that leaf traits are highly plastic within a given species and change under varying resource limitations (Bachle & Nippert, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A major goal for imaging spectroscopy is to remotely monitor dimensions of biodiversity (Cawse-Nicholson et al, 2021;Griffith et al, 2023aGriffith et al, , 2023bRocchini et al, 2022). To that end, numerous studies have sought to relate spectral diversity to taxonomic, functional, and phylogenetic diversity across scales (e.g., Cavender-Bares et al, 2017;Schweiger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Grouping traits by lineage can also explain trait variation, as seen in Edwards et al's (2007) study, where traits of Echinochloa appeared to be outliers in its C 4 PFT group, suggesting that the genus may have traits unique to its independent C 4 lineage. Furthermore, LFT approaches have the potential to be broadly applicable in other ecosystem types and for remote sensing and scaling applications (Anderegg et al, 2022;Griffith et al, 2023;R. Slapikas et al, unpublished).…”
Section: Introductionmentioning
confidence: 99%